2007
DOI: 10.1002/j.1556-6978.2007.tb00030.x
|View full text |Cite
|
Sign up to set email alerts
|

Personality: A Predictor of Theoretical Orientation of Students Enrolled in a Counseling Theories Course

Abstract: Selecting a single psychotherapeutic orientation can be a challenge for counselor education students. The authors examined the relationship between counseling theory selection and personality variables of students enrolled in a counseling theories course. A discriminant function analysis was used to identify the personality traits that would determine theoretical orientation choice. No statistically significant results were found. Results indicated that students showed no personality-based preference of theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 12 publications
2
24
0
Order By: Relevance
“…No themes were evident that indicated that participants' own personality factors were an influence in selecting a theoretical orientation (e.g. [15]). …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…No themes were evident that indicated that participants' own personality factors were an influence in selecting a theoretical orientation (e.g. [15]). …”
Section: Resultsmentioning
confidence: 99%
“…Studies on the influence of personality on theoretical orientation have been conducted (e.g. [13]), a recommendation for future research would be to look at other influences such as religious affiliation [3,4] and other factors due to the multifaceted nature of developing a theoretical orientation in counseling [15].…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
See 3 more Smart Citations